Validity of Agreements in the Digital era: Study of Electronic Contracts, Cryptocurrencies and Non-Fungible Tokens - Sopamena, Ronald Fadly (Faculty of Law, Universitas Pattimura, 2022)
Introduction: E-commerce transactions that develop, of course, bring changes to agreements that have been carried out conventionally, the digital era has finally brought about a new world called the metaverse with a number of assets in the form of objects such as Non-Fungible Tokens (NFT) and Crypto Currency that only exist in cyberspace.Purposes of the Research: The purpose of this research is to examine how the validity of agreements in the digital era, especially regarding electronic contracts and the purchase of Crypto Currency and NFT from Indonesian law persperctive.Methods of the Research: This research is descriptive analytical with a normative juridical type using primary, secondary and tertiary data from literature studies, both legislation and legal literature and other documents.Results of the Research: Both electronic contracts and electronic signatures used in e-commerce already have a legal basis so that their use is not something that is prohibited. Talking about the validity of an agreement will not be separated from Article 1320 of the Civil Code which requires 4 points that must be fulfilled in order for an agreement to be valid in the eyes of the law. This also applies to buying and selling crypto and NFT. Crypto is actually a currency, not recognized by the state. However, crypto can be traded and recognized as a trading commodity. NFT does not yet have special regulations, but the legal requirements for buying and selling NFT are still met even if the transaction uses crypto.